Model Tata Ruang Kantor Dalam Peningkatan Etos Kerja Kepala Sekolah Di SMP 4 Muhammadiyah Medan - Adinda Julia Putri; Anisah Aruan; Affiq Faeyza; Tengku Darmansah (Journal Innovation In Education, 2024)
The principal is an educational leader, the principal’s work ethic in carrying out his duties can be influenced by several things, one of which is the office layout model. A good office layout will increase the principal’s work enthusiasm. The principal’s office should not be shared with teachers or other staff. In this study, the author conducted research using interview methods with school principals, as well as conducting direct observations in the field. Based on the research results, the author found that the office space at SMP 4 Muhammadiyah Medan could not be said to be good, because the principal’s office was still attached to other teachers’ rooms, so this could affect the principal’s work ethic.